Meningococcal Vaccines of New Generations – the First 20 Years of Use - N. N. Kostyukova; V. A. Bekhalo (Эпидемиология и вакцинопрофилактика)
Relevance. Meningococcal vaccine refers to any of the vaccines used to prevent infection by Neisseria meningitidis. Therefore, there is a great scientific and practical interest in the existing and developed menicococcal vaccines.Aims the review is to provide an analysis: literature data on the effectiveness of meningococcal vaccines of new generations - conjugated polysaccharide serogroups A, C, W and Y and protein serogroup B.Conclusions. With regard to conjugated vaccines, there are a large number of reliable observations confirming the high immunological and epidemiological effectiveness of these vaccine preparations, including the prevention of bacterial carriage and the development of herd immunity. These vaccines are weakly reactogenic, and in many countries, they are introduced into national immunization programs and in some countries are used as mandatory (UK) or in connection with the existing epidemic indications. The protein «vesicle» vaccine based on serogroup B meningococcal outer membrane proteins, showed high efficacy only in those cases when the protein composition of the strain that caused the morbidity corresponded to the composition (mainly in terms of the PorA subtype antigen) of the vaccine. Genetic-engineered vaccines containing only a few serogroup B meningococcal protein antigens with or without the addition of «vesicle» proteins are difficult to evaluate due to the small number of observations associated with low serogroup В prevalence, but in Great Britain, such vaccine was also introduced as mandatory in the national immunization schedule for babies. At the same time, new vaccines of serogroup B induce immune protection against some strains of meningococcus of other serogroups C, W, and Y, and even against other species of Neisseria, in particular - gonococcus. This circumstance gives rise to hope for the development of protein meningococcal vaccines with a wider spectrum of specificity than the group, and even than the species.